RUANG KREATIF: REKREASI DI SENEN MELALUI KONSEP TERBUKA DAN MENGUNDANG - Wijaya, Gunardi Naga; Kasimun, Petrus Rudi (Jurusan Arsitektur dan Perencanaan, 2024)
The Senen area, which was once known as the center of the economy in Jakarta, is now abandoned, many of the building functions are not maintained, not keeping up with the times, and coupled with the lack of place needs for the people in Senen regarding the need for a place to relieve stress. The stress arises from the density of space and the busyness of its people. Along with the development of the era, the Senen area will become a dense place for housing, shops, and transportation centers. With the facilities in the Senen area that are quite complete, the Senen area is a suitable place to restore its image as before. From these emerging problems, an open space is needed that can be a recreation center. The lack of entertainment venues in the Senen area is the right strategy to add programs with entertainment functions. By implementing an open and inviting concept, it aims to invite people in the Senen area to have a new entertainment venue that functions as a place to pour out existing creative ideas. Using qualitative methods and figure of reasoning methods to find out what space program needs are suitable to respond to existing. problems. Keywords: Stress; Open Space; Open and Inviting Abstrak Kawasan Senen yang dahulu dikenal sebagai pusat perekonomian di Jakarta yang sekarang ditinggalkan, banyaknya fungsi bangunan yang tidak terawat, kurang mengikuti zaman dan ditambah dengan kurangnya kebutuhan tempat untuk masyarakat di Senen mengenerasiai kebutuhan tempat untuk menghilangkan rasa stress. Rasa stress yang muncul yang berasal dari kepadatan ruang dan kesibukkan dari masyarakatnya. Seiring dengan perkembangan zaman kawasan Senen akan menjadi tempat yang padat akan hunian, pertokoan, maupun pusat dari transportasi. Dengan adanya fasilitas yang ada di kawasan Senen yang sudah cukup lengkap, maka dari itu kawasan Senen menjadi tempat yang cocok untuk diangkat kembali citranya seperti dulu. Dari permasalahan yang muncul inilah dibutuhkannya ruang terbuka yang dapat menjadi pusat rekreasi. Kurangnya tempat hiburan yang ada di kawasan Senen menjadi strategi yang tepat untuk menambah program dengan fungsi sebagai hiburan. Dengan penerapan konsep terbuka dan mengundang (open and inviting) bertujuan agar mengundang masyarakat yang ada di kawasan Senen agar memiliki tempat hiburan baru yang berfungsi sebagai tempat untuk menuangkan ide kreatif yang ada. Menggunakan metode kualitatif dan metode figure of reasoning agar dapat mengetahui kebutuhan program ruang apa yang cocok untuk merespon masalah yang ada.